2013
DOI: 10.1097/pgp.0b013e31825b0585
|View full text |Cite
|
Sign up to set email alerts
|

Is the Detection of Endometrial Nerve Fibers Useful in the Diagnosis of Endometriosis?

Abstract: Laparoscopy is currently considered to be the gold standard investigation in patients suspected to have endometriosis, but this is an invasive and relatively costly procedure and there may be significant delays in diagnosis. As the eutopic endometrium is recognized to be abnormal in patients with endometriosis, it has been suggested that endometrial sampling could provide an indirect diagnostic approach. In particular, recent reports have suggested that the presence of nerve fibers within the endometrial funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…These results were confirmed in a study of 27 prospectively collected eutopic endometrial specimens using identical sampling and detection methods [ 142 ]. However, the adoption of this method in a clinical laboratory failed to recapitulate the accuracy of endometrial PGP9.5 immunohistochemistry in the diagnosis of women with endometriosis [ 143 ]. Functional endometrial layer nerve fibers assessed by PGP9.5 immunostaining were detected in 9 of 45 (22%) of histologically confirmed cases of endometriosis and in 6 of 21 (29%) of women without endometriosis.…”
Section: Endometrial Biomarkersmentioning
confidence: 99%
“…These results were confirmed in a study of 27 prospectively collected eutopic endometrial specimens using identical sampling and detection methods [ 142 ]. However, the adoption of this method in a clinical laboratory failed to recapitulate the accuracy of endometrial PGP9.5 immunohistochemistry in the diagnosis of women with endometriosis [ 143 ]. Functional endometrial layer nerve fibers assessed by PGP9.5 immunostaining were detected in 9 of 45 (22%) of histologically confirmed cases of endometriosis and in 6 of 21 (29%) of women without endometriosis.…”
Section: Endometrial Biomarkersmentioning
confidence: 99%
“…Leslie et al [18] found endometrial nerve fibers in conventional biopsy specimens of 19% of patients with and 29% of patients without endometriosis. In a group of 44 women with pelvic pain, endometrial fine nerve fibers were present in patients with and without endometriosis.…”
Section: Resultsmentioning
confidence: 99%
“…Leslie et al [13] analyzed 68 endometrial samples before surgery. They found no correlation between the presence of functional layer nerve fibers and the presenting symptoms, endometrial histology, or current hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Progesterone treatment revealed a decrease in endometrial nerve fibers, but no clinical significance was identified. [17] As a result, further studies were recommended in recent publications for these patient groups.…”
Section: Introductionmentioning
confidence: 99%